PENGARUH PENGUASAAN GERAK MELINGKAR BERATURAN TERHADAP HASIL BELAJAR FISIKA SISWA MATERI POKOK GRAVITASI SISWA KELAS XI SMA NEGERI 1 ANGKOLA BARAT - Zuliani Nasution, Unita Sukma (Jurnal Physics Education (PhysEdu), 2023)
This research aims to find out the influence of regular circular movement to the student’s achievement is gravitation of the XI SMA Negeri 1 Angkola Barat. This research is done by usng descriptive method, it is to see the description and the experiment method of both variables.The population of this research ia all of XI SMA Negeri 1 Angkola Barat. Consist of 2 classes it is 60 students. Sampel of this research is 60 students, taken by using total sampling.Based on the calculation of pre test for score for regular circular movement is 41,78, it is fail category. Based on the calculation of post test for score for regular circular movement is 66,29, it is fail it is enough category, while the mean pre test for gravitation achievement is 44,46 it is fail category. While yhe mean post test for gravitation achievement is 68,13 it is enough category. Based on the calculation in inferensial analysis, it in pre test is found that cout is 11,25 and if it is compared to t table in 5% significant it is found 2,002. After comparing t count and t table it is got that t count is greater than t table (11,25>2,002). it in pos test is found that cout is 11,37 and if it is compared to t table in 5% significant it is found 2,002. After comparing t count and t table it is got that t count is greater than t table (11,37>2,002). The hypothesis is accepted, means that there is significant influence regular circular movement to the students achievement in gravitation of the XI SMA Negeri 1 Angkola Barat.